2020
DOI: 10.5483/bmbrep.2020.53.11.114
|View full text |Cite
|
Sign up to set email alerts
|

Tat-indoleamine 2,3-dioxygenase 1 elicits neuroprotective effects on ischemic injury

Abstract: It is well known that oxidative stress participates in neuronal cell death caused production of reactive oxygen species (ROS). The increased ROS is a major contributor to the development of ischemic injury. Indoleamine 2,3-dioxygenase 1 (IDO-1) is involved in the kynurenine pathway in tryptophan metabolism and plays a role as an anti-oxidant. However, whether IDO-1 would inhibit hippocampal cell death is poorly known. Therefore, we explored the effects of cell permeable Tat-IDO-1 protein against oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The current study found that the metabolite with the most significant change in levels among the aforementioned metabolites was tryptophan, which plays a key role in cerebral ischemia. IDO enzymes are the main rate-limiting enzymes for tryptophan degradation ( 23 ). IDO enzymes consist of two members, IDO1 and IDO2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study found that the metabolite with the most significant change in levels among the aforementioned metabolites was tryptophan, which plays a key role in cerebral ischemia. IDO enzymes are the main rate-limiting enzymes for tryptophan degradation ( 23 ). IDO enzymes consist of two members, IDO1 and IDO2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well known that the MAPK (p38, ERK and JNK) signaling pathways are highly associated with oxidative stress-induced cell death ( 24-26 ). It has been reported that Tat-IDO-1 transduced into HT22 cells reduces cell death, ROS production, DNA fragmentation and H 2 O 2 -induced MAPK phosphorylation ( 23 ). Other studies have also shown that overexpression of IDO proteins inhibits the activation of MAPK signaling pathways under conditions of oxidative stress ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key enzyme in the KP, IDO1 plays a crucial role in the regulation of the KP. Hence, IDO1 should be considered a potential therapeutic target for neurological diseases (39).…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%
“…Thus PTDs have been applied as effective vehicles to deliver therapeutic molecules like protein, DNA, RNA, liposome and nanoparticles into cells because they have the ability to transduce into cells [21,22]. Among them, Tat-PTD derived from the human immunodeficiency virus is widely used to deliver the therapeutic protein into cells [23][24][25], and many groups have shown that Tat-fusion protein is transduced into a variety of cells, which were markedly protected against oxidative stress-induced cell death [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%